Six Sigma-based approach to optimise the diffusion process of crystalline silicon solar cell manufacturing. Issue 2 (7th February 2016) - Prasad, A. Guru; Saravanan, S.; Gijo, E.V.; Dasari, Sreenivasa Murty; Tatachar, Raghu; Suratkar, Prakash
Abstract : Silicon-based photovoltaics (PV) plays the dominant role in the history of PV due to the continuous process and technology improvement in silicon solar cells and its manufacturing flow. In general, silicon solar cell process uses either p -type- or n -type-doped silicon as the starting material. Currently, most of the PV industries use p -type, boron-doped silicon wafer as the starting material. In this work too, the boron-doped wafers were considered as the starting material to create pn junction and phosphorus was used as n -type doping material. Industries use either phosphorous oxy chloride (POCl3 ) or ortho phosphoric acid (H3 PO4 ) as the precursor for doping phosphorous. While the industries use POCl3 as the precursor, the throughput is lesser than that of the industries' use of H3 PO4 due to the manufacturing limitations of the POCl3 -based equipments. Hence, in order to achieve the operational excellence in POCl3 -based equipments, business strategies such as the Six Sigma methodology have to be adapted. This paper describes the application of Six Sigma Define–Measure–Analyze–Improve–Control methodology for throughput improvement of the phosphorus doping process. The optimised recipe has been implemented in the production and it is running successfully. As a result of this project, an effective gain of 0.9 MW was reported per annum.